Shoulder MRI Abnormalities in Asymptomatic Little League Baseball Players. Issue 2 (22nd February 2018) - Pennock, Andrew T.; Dwek, Jerry; Levy, Emily; Stearns, Philip; Manning, John; Dennis, M. Morgan; Davis-Juarez, Amanda; Bastrom, Tracey; Taylor, Kenneth S.
Background: Youth baseball is extremely popular in the United States, but it has been associated with shoulder pain and injury. The incidence of shoulder abnormalities in this athletic population has yet to be defined. Purpose: To examine abnormalities noted on magnetic resonance imaging (MRI) in the shoulders of asymptomatic Little League baseball players and to correlate these findings with the players' throwing history and physical examinations. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 23 Little League baseball players aged 10 to 12 years were recruited. All players underwent a comprehensive physical examination and responded to a questionnaire addressing their playing history and any arm or shoulder pain. Bilateral shoulder MRIs were performed and read in a blinded manner by 2 radiologists. Responses on the questionnaire and physical examination findings were compared between participants with and without positive MRI findings through use of chi-square test and analysis of variance. Results: The dominant arm was 8.5 times more likely to have an abnormality on MRI compared with the nondominant arm. In all, 12 players (52%) had 17 positive MRI findings in their throwing shoulder that were not present in their nondominant shoulder. These findings included edema or widening of the proximal humeral physis (n = 5), labral tear (n = 4), partial rotator thickness tear (n = 4), acromioclavicular joint abnormality (n = 2), subacromial bursitis (n = 1), and cystic change of the greater tuberosity (n = 1). Two primary risk factors were associated with an abnormal MRI: year-round play and single-sport athletes focusing solely on baseball ( P < .05). Players with no risk factors, 1 risk factor, and both risk factors had a 25%, 71%, and 100% chance, respectively, of having an abnormal MRI. A majority of players (61%) had previously experienced shoulder pain, especially pitchers throwing curveballs and sliders ( P < .05), but this was not associated with an abnormal MRI. Conclusion: Abnormalities seen on MRI involving the shoulder are common in Little League baseball players, especially those who are single-sport athletes playing year-round.